2019
DOI: 10.1051/matecconf/201929001023
|View full text |Cite
|
Sign up to set email alerts
|

From part to point cloud, the modelling of a 3D part

Abstract: The present paper focuses on the development of the composite materials in the automotiv industry by making a comparative analysis between a 3D model of the part and a real part made by a composite material, measuring the part using the point cloud. The aim is to obtain a high modeling and a more clear visualization of the composite material part.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…[4] The material we choose is used in engineering industry, in flexible manufacturing lines, where positioning platforms for car body and special conveyer for the moving car body exist, they are called conveyance station from a work station to another. [5] From the analysis of the variation graphs tensile stress -tensile strain for the UHMWPE material, it is observed that after reaching the yield stress, the tension increases continuously on a relatively full slope until reaching the maximum value where the first rupture cracks appear. The centralizing table showes the values of maximum tensile stress, load at maximum tensile stress, extention at maximum tensile stress, tensile strain at break, tensile stress at break and tensile strain at Yield, for the UHMWPE samples.…”
Section: Traction Machinementioning
confidence: 99%
“…[4] The material we choose is used in engineering industry, in flexible manufacturing lines, where positioning platforms for car body and special conveyer for the moving car body exist, they are called conveyance station from a work station to another. [5] From the analysis of the variation graphs tensile stress -tensile strain for the UHMWPE material, it is observed that after reaching the yield stress, the tension increases continuously on a relatively full slope until reaching the maximum value where the first rupture cracks appear. The centralizing table showes the values of maximum tensile stress, load at maximum tensile stress, extention at maximum tensile stress, tensile strain at break, tensile stress at break and tensile strain at Yield, for the UHMWPE samples.…”
Section: Traction Machinementioning
confidence: 99%